KNOWLEDGE TRANSFER STRATEGIES: AS AN ELEMENT OF HUMANWARE MANAGEMENT IN KNOWLEDGE ORGANIZATIONS - Acevedo, Carlos; Mejía, Aquiles; Blanco, Amanda (Revista Arbitrada Formación Gerencial, 2022)
The objective of this research is to analyze knowledge transfer strategies: as an element of the management of Humanware in Saber organizations, in order to be able to provide tools that are used by participants and facilitators in the educational process as well as investigative, Mixing the processes of management and knowledge. The research was based on the positivist paradigm with a descriptive type and a non-experimental, transversal, field design. The study was made up of teachers-facilitators and students-participants of the Universities of Norte de Santander-Colombia considering stratified probabilistic sampling, leaving a total of two hundred seventeen (217) subjects to be investigated. Its results are reflected in that the strategies for the transfer of knowledge have become a point of pressure and reference to guide the changes that the educational system has to make; In order to train the new professionals, maintaining coherence or syntony with macro structural changes, in which the characteristics of future education are involved and determinant, while management does not provide opportunities where all people acquire skills, skills as well as socio- Based on the development of programs where people and.